The Dynamic Effect of Trade Openness, Debt, and Foreign Investment in Ghana’s Economy: An ARDL Bound Testing Approach - Yeboah, Evans; Lamin, Ceesay (International Journal of Engineering and Management Sciences, 2024)
The impact of macroeconomic factors offers insight into the performance of an economy. This study investigates the dynamic short- and long-term effect of trade openness, external debt, and foreign direct investment (FDI) within Ghana's economy. Utilizing Autoregressive Distributed Lag (ARDL) bound testing and Granger causality analysis, the study examines data spanning from 1991 to 2022. The results of the ARDL cointegration test reveal a long-term relationship among the variables. However, in the short term, the findings present a mixed effect of FDI and trade openness, with both positive and negative impacts. In the long run, FDI and external debt exhibit a positive influence, whereas trade openness appears to impede economic growth. Furthermore, the Granger causality test identifies a unidirectional causality relationship between the variables and economic growth. The study suggests that the government implement investment-oriented and trade policies to stimulate economic growth.